Urgensi Penyucian Niat dalam Aktivitas Menuntut Ilmu: Studi Kualitatif terhadap Pemikiran Az-Zarnuji dalam Ta‘lim al-Muta‘allim - Risris Hari Nugraha; Muhamad Rizka Saomi; Rizqy Nur Solihat; Isop Syafei; Izzuddin Musthafa; Muhammad Faiz Ramadhan (Universitas Negeri Padang, 2025)
This research analyzes the concept of intention (niyyah), the urgency of its purification, and the relevance of Az-Zarnuji's thoughts in the book Ta‘lim al-Muta‘allim to modern Islamic education. Using a qualitative approach and library research, the study focuses on content analysis of the primary text of Ta‘lim al-Muta‘allim. Data were analyzed using the interactive model of Miles and Huberman.The results show that intention (an-niyyah) is the main spiritual and moral foundation that determines the blessing (barakah) and devotional value of seeking knowledge. Az-Zarnuji emphasizes the purification of intention (tazkiyat an-niyyah) so that the learning objective is free from worldly ambitions and directed as a means of devotion to God (Allah). A sound intention leads to beneficial knowledge (‘ilm nāfi‘) and shapes the scholar's character to be humble (tawāḍu‘) and ethical.This thought has high relevance in the context of modern education. The concept of Tazkiyat an-Niyyah can serve as the spiritual foundation that strengthens the implementation of Deep Learning, ensuring the learning process is both Meaningful and Mindful, thereby enabling the educational system to reorient itself towards the formation of a character defined by integrity and civility.